Forgiveness in Islam: Promoting A Peaceful World - Yoachim Agus Tridiatno (Universitas Islam Negeri Sunan Kalijaga, 2021)
The paper explores forgiveness in Islam starting from the Islamic bases, forgiveness as moral response, forgiveness needs repentance, and implementing forgiveness for promoting a peaceful world. It is library research based on articles and books which discussed the topics, and the secondary data about forgiveness in Islam. It aims to expose the soft side of Islam especially its struggle for peace and harmonious life.